2016
DOI: 10.1016/j.enconman.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Energy recovery from human faeces via gasification: A thermodynamic equilibrium modelling approach

Abstract: HighlightsOn dry basis, typical human faeces contain 83 wt.% organic fraction and 17 wt.% ash.The LHV of dry human faeces ranged from 19 to 22 MJ/kg, values similar to wood biomass.Syngas from dry human faeces had LHV of 15–17 MJ/kg at equivalence ratio of ∼0.31.Energy is best recovered from moist human faeces at equivalence ratio above 0.6.Recoverable exergy potential from moist human faeces can be up to 15 MJ/kg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 33 publications
4
60
0
Order By: Relevance
“…The composition results of the three samples are in agreement with composition data of similar samples published elsewhere [23]. Onabanjo et al [23] showed that average composition from a set of 12 different human faeces sample was 51 ± 2 wt.% C, 7 ± 0 wt.% H, 4 ± 1 wt.% N, 21 ± 3 wt.% O and 17 ± 1 wt.% ash (dry basis). In addition, simulant faeces prepared following the same recipe used in this work had similar ultimate composition, i.e.…”
Section: Resultssupporting
confidence: 90%
“…The composition results of the three samples are in agreement with composition data of similar samples published elsewhere [23]. Onabanjo et al [23] showed that average composition from a set of 12 different human faeces sample was 51 ± 2 wt.% C, 7 ± 0 wt.% H, 4 ± 1 wt.% N, 21 ± 3 wt.% O and 17 ± 1 wt.% ash (dry basis). In addition, simulant faeces prepared following the same recipe used in this work had similar ultimate composition, i.e.…”
Section: Resultssupporting
confidence: 90%
“…Also, biosolids are included since such residue has an important amount of organic matter, with a similar composition to human feces in terms of proximate and ultimate analysis. A few authors refer to human fecal material as a categorized biomass [6,12,14,30], but the high levels of moisture content tend to approximate their classification as a biosolid. Indeed, while eliminating the water levels, the biomass category fits with more accuracy.…”
Section: Thermogravimetric Analysis (Tga) and Differential Scanning Cmentioning
confidence: 99%
“…Some authors explored the thermochemical characterization of simulated feces on smoldering combustion [9][10][11], and gasification [6,12], but to reproduce feces is a very complex challenge considering its heterogeneous characteristics. Nevertheless, the results were very encouraging.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations